Enhancing maize growth and resilience to environmental stress with biochar, gibberellic acid and rhizobacteria - Anwar, Tauseef; Qureshi, Huma; Akhtar, Muhammad Saeed; Siddiqi, Ejaz Hussain; Fatimah, Hina; Zaman, Wajid; Alhammad, Bushra A.; Seleiman, Mahmoud F. (Frontiers in Plant Science, 2024)
Zea mays (maize) is a globally significant cereal crop with diverse applications. This study explores the impact of Cadmium (Cd) viz. 0, 6 and 12 ppm, Lead (Pb) viz. 0 and 400 ppm toxicity and drought stress (DS) on maize growth and development. Various treatments included the application of 10 ppm gibberellic acid (GA3), 0.75% biochar (BC), combined treatment of 10 ppm GA3 and 0.75% BC, application of rhizobacteria (RB) and combined treatment of 0.5% BC and RB. In the absence of Cd stress (0 Cd), germination rates were significantly enhanced by the application of 10 ppm GA3 and 0.75% BC, resulting in a 72% and 76% increase, respectively, compared to the control. Notably, combined treatment of GA3 and BC exhibited the highest enhancement with an 86% increase in germination. Under Cd stress (6 ppm Cd), both GA3 (54% increase) and BC (57% increase) individually improved germination, with combined treatment showing the largest increase (63%). DS influenced germination, with notable improvements observed with the application of 0.5% BC (50% increase) and RB (49% increase). Similarly, trends were observed in shoot and root lengths, where combined treatment of GA3 and BC resulted in the most significant improvements. The treatments positively influenced shoot and root protein, phenolics and chlorophyll contents, particularly under stress conditions. These findings highlight the potential of combined treatments, such as the application of GA3 and BC or BC with RB, in alleviating heavy metals (HMs) and DS in maize cultivation, offering valuable insights for sustainable agricultural practices. Future research should focus on longterm field trials to validate these findings and explore the mechanistic pathways involved in stress mitigation by these amendments, as well as their economic feasibility and environmental impact on a larger scale.